Articular cartilage regeneration with autologous marrow aspirate and hyaluronic acid: an experimental study in a goat model - Saw, Khay Yong; Hussin, Paisal; Loke, Seng Cheong; Goriman Khan, Mohd Azam Khan; Chen, Hui Cheng; Tay, Yong Guan; Low, Sharon; Wallin, Keng Ling; Ragavanaidu, Kunaseegaran (Elsevier, 2009)
Purpose: The purpose of the study was to determine whether postoperative intra-articular injections of autologous marrow aspirate (MA) and hyaluronic acid (HA) after subchondral drilling resulted in better cartilage repair as assessed histologically by Gill scoring.